2017
DOI: 10.1596/1813-9450-8178
|View full text |Cite
|
Sign up to set email alerts
|

Politics, Public Works and Poverty: Evidence from the Bangladesh Employment Generation Programme for the Poorest

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Despite the size of the EGPP and prevalence of other social assistance programs in Bangladesh, few studies are available to assess the program impacts and effectiveness. The most relevant study to this paper is Sharif and Ruthbah (2017), which investigated the determinants of EGPP participation among poor households and estimated its impact on household expenditure during the earlier stage of EGPP from 2010 to 2012. The study found that participation in EGPP was significantly associated with the household head's political connection to local officials and influential people in villages, which highlights the need to ensure a transparent targeting and enrollment process.…”
Section: Bangladesh's Safety Net Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the size of the EGPP and prevalence of other social assistance programs in Bangladesh, few studies are available to assess the program impacts and effectiveness. The most relevant study to this paper is Sharif and Ruthbah (2017), which investigated the determinants of EGPP participation among poor households and estimated its impact on household expenditure during the earlier stage of EGPP from 2010 to 2012. The study found that participation in EGPP was significantly associated with the household head's political connection to local officials and influential people in villages, which highlights the need to ensure a transparent targeting and enrollment process.…”
Section: Bangladesh's Safety Net Programsmentioning
confidence: 99%
“…The price of rice fluctuates, but according to Food Price Monitoring and Analysis, 1kg of rice (Boro) costs about BDT 32; thus, the benefits of 10 to 20 kg of rice per month are equivalent to BDT 320 to 640 per month.6 SeeSharif and Ruthbah (2017) for a detailed discussion on the background and political economy of the introduction of EGPP.7 The criteria state that a household cannot own more than 0.5 acre of land and the head of household must work as a day laborer. These two criteria were selected based on the finding of their close correlation with the poverty status of a household.…”
mentioning
confidence: 99%
“…A large body of evidence across numerous settings shows that cash and food transfer programs are highly effective in increasing average household consumption (Ravallion, 2016), particularly of food (Hidrobo et al, 2018), and providing a minimum level of consumption in the short term. For Bangladesh, the focus of our work, studies showing impacts on consumption and poverty include Ferré and Sharif (2014), Pradham and Sulaiman (2014), Sharif and Ruthbah (2017), and Cho and Ruthbah (2018). There is some evidence on social protection's ability to play a preventative role; see for example Knippenberg and Hoddinott (2017).…”
Section: Introductionmentioning
confidence: 99%